IMPROVING THE FUNCTIONING OF THE INTEGRATED SYSTEM FOR MANAGING LABOR AND INDUSTRIAL SAFETY IN THE OIL AND GAS INDUSTRY - Abdrakhmanov N. Kh.; Sharipov G. A.; Fedosov A. V.; Abdrakhmanova K. N; Kozlowski Waldemar (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with methodology of improving the functioning of the integrated system for managing labor and industrial safety in the oil and gas sector. This industry is represented by dangerous production facilities and improving safety production become more relevant every year. The main constituent point is an integrated system for managing labor and industrial safety. The fact is that the main production assets become out-ofdate, new technologies, normative and technical documentation changes every year. These factors require the necessity to pay attention to safety and put it in accordance with modern requirements. So safety at explosion and fire hazardous industrial facilities is a necessary element of production control. There is examined regulatory framework in the sphere of labor and industrial safety, main principles of construction and realization of an integrated managing system, types of audits, and there are also determined the main criteria for evaluating the performance of the integrated system for managing labor and industry safety.